Differentially expressed messenger RNA/proteins can distinguish teratoma from necrosis in postchemotherapy retroperitoneal lymph node dissection tissue. Issue 4 (11th December 2022) - Nestler, Tim; Kremer, Lara; von Brandenstein, Melanie; Wittersheim, Maike; Paffenholz, Pia; Wagener‐Ryczek, Svenja; Quaas, Alexander; Hellmich, Martin; Müller, Stefan; Pfister, David; Odenthal, Margarete; Heidenreich, Axel
Abstract: Background: Before postchemotherapy retroperitoneal lymph node dissection (pcRPLND), in patients with metastasized germ cell tumors (GCTs), those harboring necrosis (NEC) cannot be distinguished from those who have teratoma (TER), resulting in relevant overtreatment, whereas microRNA‐371a‐3p may be predictive for viable GCT. The purpose of this study was to explore messenger RNA (mRNA) and proteins to distinguish TER from NEC in pcRPLND tissue. Methods: The discovery cohort consisted in total of 48 patients, including 16 each with TER, viable GCT, and NEC. Representative areas were microdissected. A NanoString panel and proteomics were used to analyze 770 genes and >5000 proteins. The most significantly and differentially expressed combination of both parameters, mRNA and its associated protein, between TER and NEC was validated using immunohistochemistry (IHC) in an independent validation cohort comprising 66 patients who were not part of the discovery cohort. Results: The authors observed that anterior gradient protein 2 homolog (AGR2) and keratin, type I cytoskeletal 19 (KRT19) were significantly differentially expressed in TER versus NEC in mRNA and protein analyses (proteomics). The technical validation using IHC was successful in the same patients. These proteins were further validated by IHC in the independent patient cohort and exhibited significantly higher levels in TER versus NEC ( p < .0001; area under the curve, 1.0; sensitivity and specificity, 100% each). Conclusions: The current study demonstrated that KRT19 and AGR2 mRNA and protein are overexpressed in TER versus NEC in pcRPLND tissue and might serve as a future diagnostic target to detect TER, for instance, by functional imaging, to avoid overtreatment. Plain language summary: The proteins and the corresponding genes called AGR2 and KRT19 can differentiate between teratoma and necrosis in remaining tumor masses after chemotherapy in patients who have metastasized testicular cancer. This may be a way to improve presurgical diagnostics and to reduce the current overtreatment of patients with necrosis only, who could be treated sufficiently by surveillance. Abstract : Differentially expressed AGR2 and KRT19 can distinguish teratoma from necrosis in postchemotherapy retroperitoneal lymph node dissection tissue on messenger RNA/proteins in patients who have metastasized testicular germ cell tumors. This might be a basis to improve diagnostics and to reduce current overtreatment.